COMPARATIVE ANALYSIS OF THE USER INTERFACE OF PLATFORMS FOR DISTANCE LEARNING - Krestyanpol, Lyubov; Verkholyuk, Anastasia (Physical and Mathematical Education, 2023)
Formulation of the problem. The paper addresses the issue of the convenience of user interfaces of platforms for distance learning. In modern realities, education in Ukraine is changing and modernizing. This is due not only to the informatization of society but also to the Covid-19 pandemic and the war. This influenced the educational process and changed it. The usual offline learning has switched to online mode using a variety of software. However, it is not always easy to master and use new software, which can significantly affect the quality and effectiveness of learning and teaching. Materials and methods. Analysis and synthesis of theoretical information were carried out; testing of user interfaces was carried out, an online survey was conducted and the results of surveys were processed. Experimental research base: students and teachers of the Department of Applied Linguistics took part in the experiment. The total number of participants is 120 students and 8 teachers. Results. The paper analyzes the interfaces of Moodle and Google Classroom distance learning platforms. The main functional modules of the systems are described, and their advantages and disadvantages are indicated (functionality, efficiency, utilitarianism, and software satisfaction are compared). For testing systems, electronic courses have been developed that have been implemented since 2019. The results of surveys of teachers and students on the ergonomics of platforms are presented. Analysis of empirical data showed a change in factors affecting the effectiveness of distance learning: distance learning platforms and the motivation of applicants and teachers. Conclusions. The analysis made it possible to optimally select distance education platforms by the educational component. The main problematic issues that arose in the process of learning from applicants and teachers are identified.